Multiscale study on coal pillar strength and rational size under variable width working face - Huang, Peng; Zhang, Qiang; Xie, Jing; Li, Junmeng; Zhang, Qi; Li, Meng; Simao, Francisco Chano (Frontiers in Environmental Science, 2024)
The reasonable size of the coal pillar in the working face is usually the most critical aspect in coal mining, which is related to the deformation of the surrounding rock of the roadway and the degree of damage to the coal pillar during the coal resource extraction process. The reasonable-size design of coal pillars usually adopts methods such as strength and elastic core zone calculation. However, for the remaining coal resources, the width of the working face is often unequal, and widening or narrowing the working face can significantly change the reasonable size of the coal pillar. In the laboratory, uniaxial compression tests were conducted on coal samples with different aspect ratios. Based on the possible sizes of coal pillars in coal mines, four three-dimensional numerical models of coal pillar compression with different aspect ratios were established. Obtained the failure characteristics and strength of coal pillars with different aspect ratios and provided the strength formula and aspect ratio calculation formula for coal pillars. A mechanical roof model for widening the working face was established, and the relationship between coal pillar strength and working face width was proposed. The strength of coal pillars increases with the increase of aspect ratio. The length of the working face and the aspect ratio of the coal pillar were calculated using the coal pillar strength formula. The width of the working face has increased from 63 m to 160 m, and the size of the coal pillar has increased from 3.6 m to 13.4 m, which has improved the resource recovery rate of the coal pillar. According to the deformation monitoring of the A503 working face roadway that there is no evidence of roof caving or sheeting, and the roadway’s maximum deformation is 147.3 mm, which proves that the width of the coal pillar is suitable for the mining requirements of uneven working faces. This provides important theoretical support for reasonably determining the size of coal pillars and improving the utilisation rate of irregular coal resources.